2001
DOI: 10.1590/s0100-41582001000200014
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of sorghum genotypes to the anthracnose fungus Colletotrichum graminicola

Abstract: The reactions of 22 sorghum (Sorghum bicolor) genotypes to six previously identified races of the sorghum anthracnose fungus Colletotrichum graminicola, were evaluated under greenhouse and field conditions. Races were inoculated in separate tests in the greenhouse. In the field, spreader rows of a susceptible genotype were artificially inoculated with a mixture of the six races of the pathogen. In the greenhouse tests, nine genotypes showed resistance to all six races. In the field high levels of dilatory resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 7 publications
(7 reference statements)
0
23
0
Order By: Relevance
“…Some alternatives have been studied to obtain a more stable resistance to this pathogen, for example the selection of genotypes with dilatory resistance, characterized as a higher capacity of some genotypes for limiting disease progress (Casela et al 1993). However, this resistance has also proven to be somewhat unstable, due to pathogen population variability (Guimarães et al 1998, Casela et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Some alternatives have been studied to obtain a more stable resistance to this pathogen, for example the selection of genotypes with dilatory resistance, characterized as a higher capacity of some genotypes for limiting disease progress (Casela et al 1993). However, this resistance has also proven to be somewhat unstable, due to pathogen population variability (Guimarães et al 1998, Casela et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…More than 40 races/pathotypes have been reported from different geographical areas of the world using different sets of putative host differentials (Casela and Ferreira, 1995;Marley et al, 2001Marley et al, , 2004Mathur et al, 2002;Rooney et al 2002). The C. graminicola races were first reported in the United States in 1967 (Haris and Johnson, 1967).…”
Section: Physiological Racesmentioning
confidence: 99%
“…Attempts were made to increase the durability of the resistance to anthracnose in sorghum. Strategies such as dilatory resistance, which reduces the rate of development of the disease (Guimaraes et al, 1998), identification of and dissociation of virulence in the population of the pathogen (Casela et al, 2001a) and the use of the mixtures of cultivars (Guimaraes et al, 1998). The use of hybrid development resulting from the combination of male sterile (A) and the restorer (R) lines against which there is no virulence association in the pathogen population seemed to the trick of reducing the disease development.…”
Section: Host Plant Resistancementioning
confidence: 99%
“…in Kabat and Bubák) is the fungal pathogen responsible for sorghum anthracnose (Crouch et al, 2006) and was first reported in Togo, West Africa in 1902 (Thakur and Mathur, 2000). The disease occurs worldwide, but is more commonly observed in tropical or subtropical environments where frequent rainfall, high relative humidity and warm temperatures enhance the development and spread of the disease (Casela et al, 2001;Hess et al, 2002;Marley et al, 2001;Néya and Le Normand, 1998;Ngugi et al, 2002;Thakur and Mathur, 2000;Thomas et al, 1996;Valério et al, 2005). In the United States, anthracnose is more prevalent in the Southern Plains and Southeastern States (Rosewich et al, 1998;Cardwell et al, 1989).…”
Section: Introductionmentioning
confidence: 99%